Tafsir Digital: Antara Adaptasi dan Krisis Otoritas Keagamaan - Istiqomah, Dina; Rusidi, Muhammad; Yensi, Opi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study evaluates the dynamics of digital Qur`anic exegesis within the framework of adaptation and the crisis of religious authority in the age of social media. Employing a qualitative-descriptive approach using netnography and content analysis, the research explores tafsir content on Instagram, YouTube, and TikTok. The findings indicate that digital tafsir expands public access to the Qur`an in visual, contextual, and interactive ways through infographics, short videos, and animations based on digital hermeneutics. However, there is a significant shift in authority, from classical scholarly lineage (sanad) to algorithmic authority, where popularity and engagement metrics determine legitimacy. The study reveals the ambivalence of digital tafsir, while innovative, it is also vulnerable to epistemological fragmentation. Strengthening Islamic literacy and constructing a hybrid authority model are therefore necessary. This research contributes to the integration of Qur`anic studies, digital media theory, and religious authority in an interdisciplinary framework.